Reducing Phenanthrene Contamination in Trifolium repens L. With Root-Associated Phenanthrene-Degrading Bacterium Diaphorobacter sp. Phe15 - Zhao, Hui; Gu, Yujun; Liu, Xiangyu; Liu, Juan; Waigi, Michael Gatheru (Frontiers in Microbiology, 2021)
Some root-associated bacteria could degrade polycyclic aromatic hydrocarbons (PAHs) in contaminated soil; however, their dynamic distribution and performance on root surface and in inner plant tissues are still unclear. In this study, greenhouse container experiments were conducted by inoculating the phenanthrene-degrading bacterium Diaphorobacter sp. Phe15, which was isolated from root surfaces of healthy plants contaminated with PAHs, with the white clover (Trifolium repens L.) via root irrigation or seed soaking. The dynamic colonization, distribution, and performance of Phe15 in white clover were investigated. Strain Phe15 could efficiently degrade phenanthrene in shaking flasks and produce IAA and siderophore. After cultivation for 30, 40, and 50 days, it could colonize the root surface of white clover by forming aggregates and enter its inner tissues via root irrigation or seed soaking. The number of strain Phe15 colonized on the white clover root surfaces was the highest, reaching 6.03 Log CFU·g-1 FW, followed by that in the roots and the least in the shoots. Colonization of Phe15 significantly reduced the contents of phenanthrene in white clover; the contents of phenanthrene in Phe15-inoculated plants shoots and roots were reduced by 29.92-43.16% and 41.36-51.29%, respectively, compared with the Phe15-free treatment. The Phe15 colonization also significantly enhanced the phenanthrene removal from rhizosphere soil. The colonization and performance of strain Phe15 in white clove inoculated via root inoculation were better than seed soaking. This study provides the technical support and the resource of strains for reducing the plant PAH pollution in PAH-contaminated areas.